A Therapeutic Insole Device for Postural Stability in Older People With Type 2 Diabetes. A Feasibility Study (SENSOLE Part I) - Regueme, Sophie C.; Cowtan, Charles; Sedgelmaci, Mohamed Y.; Kelson, Mark; Poustis, Joël; Rodriguez-Mañas, Leocadio; Sinclair, Alan J.; Dallaudière, Benjamin; Bourdel-Marchasson, Isabelle (Frontiers in Medicine, 2019)
The application of a stochastic mechanical noise has been shown to improve plantar touch sensitivity in patients with diabetic neuropathy and balance control. The present work aimed to test the feasibility of a specially designed vibrating device on gait and posture in older patients with type 2 diabetes with special interest on potential side effect (sensation of needles or tingling, dizziness or falls) before further investigations. For this, gait and balance tests were performed in 29 older out and in-patients (mean age 84 years, Barthel index ≥ 60/100) immediately before and after a 19 minutes plantar vibrating sequence, as well as 15 minutes after. These tests included posturographic measurements under eyes closed and static conditions and clinical gait tests (Short Physical Performance Battery and Timed-Up and Go tests). The results showed that no side effect was measured immediately, 15 minutes and up to 30 days after the vibration sequence. Besides, postural and clinical gait tests showed global positive effects at immediate and 15 minute follow-up. Further investigation are now necessary to determine whether a daily stimulation sequence for a given time would lead to long-term positive effects on daily living (NCT01654341; https://clinicaltrials.gov/ct2/show/NCT01654341)